2021
DOI: 10.4018/ijhcitp.2021070104
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Maturity and Employer Satisfaction

Abstract: The present research study examines emotional maturity and its relationship with employer satisfaction in recruiting fresh engineering Information Technology graduates. Four hundred sixty-five employers of multinational and national information technology companies in India were considered as respondents. These employers conduct the campus placement drives in the public and private technical universities of India for the recruitment of fresh engineering graduates with specialization in information technology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Emotional maturity is a person's ability to control, understand, and express feelings healthily and productively. The results of the study conducted by Tandon et al showed four dimensions of emotional maturity: emotional stability, emotional development, social adjustment, and personality integration (Tandon et al, 2021).…”
Section: Emotional Maturity In Receiving Informationmentioning
confidence: 99%
“…Emotional maturity is a person's ability to control, understand, and express feelings healthily and productively. The results of the study conducted by Tandon et al showed four dimensions of emotional maturity: emotional stability, emotional development, social adjustment, and personality integration (Tandon et al, 2021).…”
Section: Emotional Maturity In Receiving Informationmentioning
confidence: 99%
“…Employees use a computer-mediated social network that is built on technology. Facebook, Whatsapp and Cyberdating sites for example, can be used to express personal feelings with friends and colleagues (Waite and Joyner, 2001;Hu and Kellinger, 2008;Tarafdar, et al, 2020;Pathak, 2021;Tandon et al,2021). Maximum interactions through the social exchange process increases employee proximity, which can lead to more happiness and excitement in living together (Sledgianowski and Kulviwat, 2008;Rosen and Sherman, 2006).…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…It changes the thought process of an individual and makes everything appear negative. There can be multiple sources of negativity -mistreatment, misunderstanding, a feeling of betrayal, miss recognition, mismanagement in life, jealousy, or just the mere attitude of a person (9)(10)(11). Organizations may experience environments that mitigate the negative reactions, feelings and thoughts of few employees.…”
Section: Introductionmentioning
confidence: 99%
“…Organizations may experience environments that mitigate the negative reactions, feelings and thoughts of few employees. Many organizations may not know how to handle workplace negativity (9,10,11). If workplace negativity goes unchecked, it may result into workplace toxicity and an unhealthy working environment for everyone.…”
Section: Introductionmentioning
confidence: 99%